2015
DOI: 10.3389/fmicb.2015.00264
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive cell: bacterial behavior reconsidered

Abstract: Research on how bacteria adapt to changing environments underlies the contemporary biological understanding of signal transduction (ST), and ST provides the foundation of the information-processing approach that is the hallmark of the ‘cognitive revolution,’ which began in the mid-20th century. Yet cognitive scientists largely remain oblivious to research into microbial behavior that might provide insights into problems in their own domains, while microbiologists seem equally unaware of the potential importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
249
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 254 publications
(251 citation statements)
references
References 170 publications
(236 reference statements)
0
249
0
2
Order By: Relevance
“…Recently it is emerging that all cells [25] demonstrate basal cognition [8,14,16,23,2633]. Indeed, it has been argued that life should properly be defined through the property of self-referential cognition [31,34].…”
Section: The Cell In the 21st Centurymentioning
confidence: 99%
See 4 more Smart Citations
“…Recently it is emerging that all cells [25] demonstrate basal cognition [8,14,16,23,2633]. Indeed, it has been argued that life should properly be defined through the property of self-referential cognition [31,34].…”
Section: The Cell In the 21st Centurymentioning
confidence: 99%
“…Indeed, it has been argued that life should properly be defined through the property of self-referential cognition [31,34]. Furthermore, recent advances have also revealed that neuronal aspects and cognitive capacities are valid concepts for unicellular organisms too [14,16,22,35]. Even bacteria show sensory complexity and sensory-motor circuits between plasma membrane-based sensors and correspondent motor responses of their flagella modulated by previous experiences [14,36].…”
Section: The Cell In the 21st Centurymentioning
confidence: 99%
See 3 more Smart Citations